The Correlation of Scientific Reasoning and Argumentation (SRA): An Analysis into Prospective Biology Teachers in Plant Physiology - Maisuna Kundariati; Herawati Susilo; Balqis Balqis (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This study aimed to investigate the correlation of scientific reasoning and argumentation into prospective biology teachers in plant physiology discourse. This study was conducted at September-December 2021 through blended learning. Thirty prospective biology teachers get involved as participant in this research. Scientific reasoning and argumentation intervention trough PBL and measure by essay tests. Scientific reasoning indicator follows AACU. While scientific argumentation follow TAP. This research found there is correlation between scientific reasoning and argumentation, with R value of 0.556 which means that scientific reasoning skills and scientific argumentation are moderately correlated. The contribution of scientific reasoning to scientific arguments is 30,9% while the rest is explained by other factors.